The Script of Jonathan Swift and Other Essays - Leslie, Shane (Publications of the A.S.W. Rosenbach Fellowship in Bibliography, 2017)
Identification and points of Swift's handwriting, "the Rarest Irish Books" of the seventeenth century, and the legend of St. Patrick's Purgatory.